THE EFFECT OF TIKTOK FITNESS CONTENT ON EXERCISE INTENTION AMONG UFM STUDENTS - TRIEU LE HUU; Ho Trung Nghi (Journal of Health and Recreation Physical Education (JHRPE), 2026)
TikTok has become one of the most popular social media platforms among university students and an important channel for disseminating fitness-related information. This study aims to examine the effect of TikTok fitness content on exercise intention among students at the University of Finance and Marketing (UFM), Vietnam, and to investigate the mediating role of exercise motivation. A quantitative research approach was employed using a structured questionnaire administered to 452 students. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Perceived Usefulness, Entertainment Value, and Social Interaction significantly influence Exercise Motivation, while Exercise Motivation has the strongest positive effect on Exercise Intention. In addition, Perceived Usefulness and Social Interaction directly affect students’ intentions to engage in regular physical activity. The proposed model explains 58.3% of the variance in Exercise Motivation and 64.1% of the variance in Exercise Intention. These findings suggest that TikTok fitness content can serve as an effective digital tool for enhancing exercise motivation and promoting active lifestyles among university students. The study contributes to the literature on social media and health behavior and provides practical implications for universities, physical education instructors, policymakers, and fitness content creators.